Alternately Intercalated Heterostructures of Carbon and MoS2 Monolayers as Saturable Absorber for Ultrashort Femtosecond Mode‐Locked Lasers. Issue 19 (16th July 2021) - Jing, Laiying; Wang, Yiran; Lian, Gang; Zhang, Baitao; Cui, Deliang; He, Jingliang; Wang, Qilong; Wong, Ching‐Ping
Abstract: 2D van der Waals (VDWs) heterostructures have attracted much attention due to their exotic electronic and optical properties, which provide a new platform for material science and device fabrication. In this work, by coupling atomic interface engineering, an alternately intercalated superstructure of carbon and MoS2 monolayers (m‐C/MoS2 ) is designed as a novel saturable absorber (SA) for mode‐locked ultrafast laser generation. The novel intercalated structures exhibit excellent properties including wide bandgap, fast inter‐ and intra‐band carrier relaxation time, and superior saturable absorption characteristic, etc. Consequently, a continuous wave mode‐locked Yb:CALGO bulk laser with pulse width as short as 92 fs is achieved by using the prepared m‐C/MoS2 SA mirror, which is much shorter than those obtained with other reported 2D materials. This study provides a valuable strategy for the development of ultrashort pulse femtosecond lasers. The novel VDWs heterostructures also open new avenues toward advanced photonic devices. Abstract : An alternately intercalated superstructure of carbon and MoS2 monolayers (m‐C/MoS2 ) has been designed by coupling atomic interface engineering. A continuous‐wave mode‐locked Yb:CALGO bulk laser with pulse width as short as 92 fs has been achieved by using the prepared m‐C/MoS2 saturable absorber mirror.